Generation of definitions for a school dictionary of sexuality - Piedra Matamoros, Esteban (2021)
The joint work of disciplines such as Computer Science and Linguistics has resulted in the innovation of technological tools for searching, selecting and organizing written information found on the Internet. The aim of this article is to make a contribution from Linguistic Engineering through a tool that generates definitions automatically from conceptual information, contexts of use and linguistic patterns. The possibility of extracting information from a corpus with marks that indicate whether it is academic, colloquial or other information allows us to classify their defining contexts and automatically generate different types of dictionaries and glossaries aimed at different audiences and with different purposes. This work arose thanks to the support provided by the creation of a methodological tool selects the necessary information for the conformation of a textual corpus compiled from the Internet, which has resulted in the preparation of a specialized “dictionary of sexuality” for a group of Mexican schoolchildren. With this dictionary, we intend to create new materials that lead to the reduction of sexually transmitted diseases, unwanted pregnancies and sexual violence in this segment of the population.